ID THE MANTA : MANTA SIGHTINGS IN MANTA SANDY - RAJA AMPAT, WEST PAPUA-INDONESIA - Hidayati Azizah; Maulita Sari Hani; Ronal Mambrasar (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2019)
Manta ray (Mobula alfredi and Mobula birostris) is an endangered species that protected by international and national law. This species is vulnerable because of commercial fisheries and anthropogenic threats. These threats have impacted the species population worldwide. Raja Ampat is home for both species of the manta ray, and the area is protected with conservation status. Manta Sandy is located in Dampier Strait, is a popular dive site in Raja Ampat visited by thousands of tourist per year. It is vital to ensure the manta sightings in this area to maintain the tourist volume for local economic benefits. Utilization of photo ID and mark-recapture technique conducted to document the spots on the belly of manta ray that identify a unique pattern of each fish. This study conducted in low season from July to August 2018 for 15 days from 08.00-16.00 used two cameras of go pro hero 4 with extra battery power. The result documented time of manta sightings and species characteristic (size, sex, species, behavior, and color morphology). The camera trap recorded four manta rays where the two of them were new identified individuals.